2007
DOI: 10.3184/030823407x209660
|View full text |Cite
|
Sign up to set email alerts
|

EPR Studies on Carboxylic Esters. Part 17.1 EPR Spectra and Spin Densities in the Radical Anions of Thio and Dithiocoumarins

Abstract: The radical anions of 4-methyl-1-thiocoumarins and 4-methyl-1-thio-2-thionocoumarins are generated by internal electroreduction and studied by EPR spectrosopy. The spin density distribution is evaluated from the proton hfs coupling constants and by MO calculations. The radical anions of the corresponding coumarins and 2-thionocoumarins are not persistent enough for EPR spectroscopic measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 15 publications
(12 reference statements)
1
10
0
Order By: Relevance
“…This shift can be explained by the enhanced polarisability of sulfur as compared with oxygen and, in particular, of the thiocarbonyl group versus the carbonyl group, which facilitates the uptake of an electron into the molecule. We have observed this effect also in the coumarin series 2 and in open-chain esters and their sulfur analogues. [5][6][7][8][9] Furthermore, a significant shift in the same direction occurs between the isocoumarins 1-4 and the corresponding benzocoumarins 5-8.…”
Section: Resultssupporting
confidence: 54%
See 3 more Smart Citations
“…This shift can be explained by the enhanced polarisability of sulfur as compared with oxygen and, in particular, of the thiocarbonyl group versus the carbonyl group, which facilitates the uptake of an electron into the molecule. We have observed this effect also in the coumarin series 2 and in open-chain esters and their sulfur analogues. [5][6][7][8][9] Furthermore, a significant shift in the same direction occurs between the isocoumarins 1-4 and the corresponding benzocoumarins 5-8.…”
Section: Resultssupporting
confidence: 54%
“…This effect should be due to the more extended p-electron system of the latter with a smaller HOMO-LUMO difference. Remarkably, the reduction potentials E ½ of the benzocoumarins are similar to E ½ of the corresponding coumarin derivatives 2 whereas the E ½ -values of the isocoumarins deviate significantly. Thus, in terms of the SET step, the benzocoumarin system is obviously more closely related to the coumarin than to the isocoumarin system, each of which formally represents a constituent of the benzocoumarin system.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…For the chosen aryl halides, all reported reduction potential values were determined using the same Ag/AgBr system, in which the potential of the Ag/AgBr system was estimated at -520 mV vs. SCE or -276 mV vs. NHE. [31,32] In addition to 1, the aryl halides (3-10) used in this study are shown in Scheme 2.…”
Section: Optimizationmentioning
confidence: 99%